European agencies : law and practices of accountability - Busuioc, Madalina (Oxford : Oxford University Press, 2013)
European agencies have been created at a rapid pace in recent years in a multitude of diverse fields from pharmaceuticals to financial supervision. This book examines how the accountability system of these agencies operates formally and in practice studying the legal provisions in place and their de facto implementation.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Administrative agencies -- Europe; Liability (Law) -- Europe; Law; Laws of specific jurisdictions & specific areas of law